Experimental study on transient pressure induced by high-speed train passing through an underground station with adjoining tunnels. Issue 224 (May 2022) - Li, Xiaofang; Wu, Zaixin; Yang, Jizhong; Zhang, Lei; Zhou, Dan; Hu, Tianen
Abstract: Transient pressure variations on train and platform screen door (PSD) surfaces when a high-speed train passed through an underground station and adjoining tunnel were studied using a moving model test device based on the eight-car formation train model. The propagation characteristics of the pressure wave that was induced when the train passed through the station and tunnel at a high speed were discussed, and the effects of the train speed and station ventilation shaft position on the surface pressure distribution of the train and PSDs were analyzed and compared. The results showed that the pressure fluctuation law is different for the train and PSD surfaces, and the peak pressure increases significantly with an increase in the train speed. Ventilation shafts changed the pressure waveform on the surface of the train and PSDs and greatly reduced the peak pressure. A single shaft at the rear end of the platform and a double shaft at the station had the most significant effect on relieving transient pressure on the surface of the train and PSDs, respectively. Compared with the case with no shaft, these two shafts reduced the maximum amplitude pressure variation of the train and PSD surfaces by 46.3% and 67.4%, respectively. Highlights: A 1:30 moving model experiment realized the movement of high-speed train passing through an underground station. Transient pressure variations on train and platform screen door surfaces were studied. The propagation characteristics of the pressure wave were discussed. Train speed and station shaft position significantly affected the pressure waveform and peak pressure.